The effect of basalt fiber reinforcement at different ratios on the unconfined compressive strength of kaolin - Gurocak, Zulfu; Topcuoglu, Yasemin Aslan (My University, 2024)
There are many materials used for stabilization or reinforcement of low strength soils. While additives such as fly ash, lime, tuff, silica fume are preferred in stabilization works, fibers are used in reinforcement works. The use of fiber, which has emerged as an alternative to traditional methods, has become widespread. The most preferred fiber types in soil reinforcement are glass, carbon, polypropylene and basalt fibers. Basalt fiber, which is produced from basalt rock and widely distributed in nature, was chosen as a reinforcement material in this study, which is increasingly used due to its high strength, economic, environmentally friendly, natural and many other superior properties. The aim of this study is to examine the effects of basalt fiber ratio on strength in low plasticity kaolin clay reinforced with basalt fiber. For this purpose, unconfined pressure tests were carried out on cylindrical samples prepared by adding 6 mm long basalt fiber at different rates to clay and compressing it at optimum water content. In the samples reinforced with basalt fiber, the maximum strength was obtained from the sample which has 2 % basalt fiber ratio. It was determined that the strength decreased in samples with higher basalt fiber content.
Keywords: Basalt fiber; Reinforcement; Kaolin clay; Unconfined compressive strength